The Sandman. Book two - Gaiman, Neil (The Sandman, 2022)
Morpheus of the Endless must journey into Hell to rectify a ten-thousand-year-old injustice. But that means traveling through the realm of Lucifer, who after their last encounter swore he would destroy the King of Dreams...